Symmetric Two-Way Communication Strategy in Overcoming the Food Colonisation Polemic: A Case Study of Dara Sarasvati's Humanitarian Action in Papua - Suci Febiyanti; Rezka Nur Aulia; Marini Sayuti (Riviera Publishing, 2025)
This study analyzes the application of Two-Way Symmetric communication strategies in overcoming food colonisation polemics that emerged from content creator Dara Sarasvati's humanitarian actions in Papua in May 2025. This issue develops when the narrative of food aid distribution is considered to have the potential to replace local food and trigger public criticism related to covert food colonization. The research uses a descriptive qualitative approach with data collection techniques through social media content analysis, activity documentation, and literature studies. The results show that the application of the Two-Way Symmetric communication model is effective in mitigating issues through the direct involvement of local communities as parallel partners, collaborative content production, and culturally sensitive approaches. This strategy is realized through workshops on economic empowerment of Papuan mothers, transparency of public communication, and strengthening the local food system. The findings indicate that participatory and inclusive communication is able to transform negative perceptions into support for sustainable humanitarian action. The implications of the research contribute to the development of ethical and responsive crisis communication practices to sensitive issues in customary territories, as well as become a reference for communication practitioners in handling public figure controversies in the digital era.